An analysis of the tax consequences of the double tax agreement between South Africa and the Democratic Republic of Congo - Mkabile, Nwabisa (Rhodes University, Faculty of Commerce, Department of Accounting, 2015)
As a result of the different tax systems adopted by countries, foreign-sourced income earned by taxpayers may be subject to double taxation. This may therefore impede cross-border trade and investment. Double taxation relief is provided unilaterally, in terms of a country's domestic laws or bilaterally in terms of Double Taxation Agreements. South African residents earning income from the Democratic Republic of Congo may be subject to tax in both countries. To eliminate such double taxation the South African Income Tax Act, No 58 of 1962, provides for unilateral relief from double taxation in the form of exemptions, rebates and deductions. The double tax agreement between South Africa and the Democratic Republic of the Congo came into effect recently and double taxation relief for South African residents is now also available in terms of tax treaty law. The objective of the research was to determine whether the combination of the unilateral measures and the double tax agreement provide relief in respect of all types of income earned by South African residents in the Democratic Republic of the Congo. It was concluded that the double tax agreement, together with the unilateral relief provided for in the Income Tax Act will grant relief for all types of income earned by South African residents in the Democratic Republic of the Congo.
Keywords: Double taxation -- South Africa; Double taxation -- Congo (Democratic Republic); Income tax -- South Africa -- Foreign income; Income tax -- Congo (Democratic Republic) -- Foreign income